Adaptive Speed Controller for Industrial Gas Turbine Based on Valve Positioner Reference Model - Jonathan, A. E.; Olubiwe, M.; Okozi, S. O.; Mbonu, E. S. (Darul Yasin Al Sys, 2025)
Research on speed control has advanced considerably, with continued efforts to address challenges related to load–frequency variation in power systems and gas turbines. This paper proposes a novel speed control system for heavy-duty gas turbines (HDGT) using an adaptive-like Proportional–Integral–Derivative (PID) controller integrated with a valve positioner reference model. The dynamic model of HDGT load–frequency operation was developed, alongside control models for model reference adaptive control (MRAC) and conventional PID. A composite multi-loop control structure combining MRAC and PID was then designed. Simulation results demonstrate that the proposed MRAC–PID system achieved rise times of 1.6074 s at no load and 1.5958 s at full load torque, settling times of 4.9584 s and 5.6801 s, and overshoot values of 4.9475% and 6.0385%, respectively. Overall, the composite system outperformed standalone MRAC and PID controllers, offering more adaptive and robust speed regulation under varying load–frequency conditions in HDGT operation. The findings highlight the potential of MRAC–PID control strategies to enhance gas turbine performance and reliability in power systems.